Voltage Sag immunity testing for AC contactors in industrial environment - Hazri Dahalan, Razip; Abu Zaharin, Ahmad (Springer Singapore, 2020)
The voltage sag is one of the prominent power quality issues faced by industrial consumers in Malaysia. Frequent voltage sag incidences have caused sensitive equipment to trip causing significant production losses. One of the identified weak link is the AC contactor. In addition, there are many ageing contactors which are still in service in the industry due to their robust design and long lifetime. This paper aims to study the immunity of voltage sag of AC contactors which are installed in a petrochemical plant. New and ageing contactor s have been chosen to undergo practical testing. A well-defined test procedures are carried out based on the IEC 61000-4-11 standard. The AC contactors were exposed to rectangular voltage sag with variations in magnitude, duration and point on wave. The results are compared to IEC 61000- 4-37 voltage tolerance curve. New contactor’s voltage tolerance curve exhibits nearly consistent response and slight deviation between different points on wave. It also recorded minimum sensitivity at voltage sag magnitude of 25%. On the other hand, ageing contactor exhibit mixed conformity to the IEC curve, with minimum sensitivity at 55% of voltage sag magnitude. To summarise, the ageing contactor is more sensitive to voltage sag magnitude and point on wave has little influence to the voltage tolerance curve of the new contactors.